Novel Shikonin Derivatives Targeting Tubulin as Anticancer Agents. (3rd July 2014) - Guo, Jing; Chen, Xiao‐Feng; Liu, Jing; Lin, Hong‐Yan; Han, Hong‐Wei; Liu, Hong‐Chang; Huang, Shou‐Cheng; Shahla, Baloch K.; Kulek, Andrew; Qi, Jin‐Liang; Wang, Xiao‐Ming; Ling, Li‐Jun; et al.
<x xml:space="preserve">Abstract</x> In this study, we report the identification of a new shikonin‐phenoxyacetic acid derivative, as an inhibitor of tubulin. A series of compounds were prepared; among them, compound 16 [(R) ‐1 ‐ (5, 8‐ dihydroxy‐1, 4‐ dioxo‐1, 4‐ dihydronaphthalen‐2‐yl)‐4‐methylpent‐3‐enyl 2‐ (4‐ phenoxyphenyl) acetate] potently inhibited the function of microtubules, inducing cell growth inhibition, apoptosis of cancer cell lines in a concentration and time‐dependent manner. Molecular docking involving 16 at the vinblastine binding site of tubulin indicated that a phenoxy moiety interacted with tubulin via hydrogen bonding with asparaginate (Asn) and tyrosine (Tyr). Analysis of microtubules with confocal microscopy demonstrated that 16 altered the microtubule architecture and exhibited a significant reduction in microtubule density. Cell cycle assay further proved that HepG2 cells were blocked in G2/M phase. Our study provides a new, promising compound for the development of tubulin inhibitors by proposing a new target for the anticancer activity of shikonin.